Start: A Platform For Empowering Talent and Facilitating Industry Collaboration - Azzahra, Putri Rakhena; Darlene, Denasha; Edrifian, Salman Zufarian (Journal of Business, Management, and Social Studies, 2021)
Objective – The primary objective is to create a centralized platform that efficiently connects entertainment industry professionals with job opportunities. Methodology – This study analyzes user interactions to understand platform usage patterns and identify areas for improvement, monitors key performance indicators (KPIs) to measure platform effectiveness and user satisfaction, and refines the platform based on data insights and user feedback. Findings – Data insights and user feedback can reveal critical information about platform performance, user behavior, and areas for improvement. Potential findings could include user behavior, platform performance, user satisfaction, and using findings to improve the platform. Novelty – The specific focus on the entertainment industry and the inclusion of both performers and technical crew as job seekers is a potential area of novelty.